1993
DOI: 10.1063/1.858617
|View full text |Cite|
|
Sign up to set email alerts
|

A large-eddy simulation scheme for turbulent reacting flows

Abstract: A general methodology is developed for simulating complicated reacting flow problems. This method combines the large-eddy simulation (LES) technique with the existing probability density function (PDF) approach for turbulent reacting flows and provides a closed form representation for all terms that are involved in the simulations. Some other issues related to this problem are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(130 citation statements)
references
References 13 publications
0
129
0
Order By: Relevance
“…(1), a density-weighted sub-grid (or filtered) PDF for the N S +1 scalar quantities can be defined as follows [34]:…”
Section: Filtered Probability Density Functionmentioning
confidence: 99%
“…(1), a density-weighted sub-grid (or filtered) PDF for the N S +1 scalar quantities can be defined as follows [34]:…”
Section: Filtered Probability Density Functionmentioning
confidence: 99%
“…He showed that the use of this methodology offers for reacting flow simulations the same advantage as the use of PDF methods: chemical reactions appear in a closed form. Gao and O'Brien [5] developed a transport equation for the scalar FDF and offered suggestions for modeling of the unclosed terms in this equation.…”
Section: Introductionmentioning
confidence: 99%
“…19 This is the most elementary form of the model, [20][21][22][23][24] and has experienced widespread applications for LES of a variety of reactive flows. Some examples are in Refs; see Ref.…”
Section: Scalar-fdf (S-fdf and S-fmdf)mentioning
confidence: 99%